Relaciones comerciales entre México y España: el problema de la diversificación comercial, 1994-2006 - Gaytán Gómez, Oriana Zaret (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
This research explores trade relations between Mexico and Spain, and gives an explanation to the phenomenon of non-existence of commercial diversification into products exported from Mexico to this nation. This work is divided in two sections, the first contains the answer to the formulation of the first research hypothesis, which explains the problem of diversification of trade, through the results of the Revealed Comparative Advantages (RCA) index, which exposed a low competitiveness in Mexican products that does not allow their incursion into the Spanish market. The second study complements the first, and indicates that the need of energy in Spain, force to this country to demand more oil products that non-oil from Mexico. This fact impedes the achievement of diversification of exports to Spain from our country. We concluded that the low competitiveness of Mexican non oil products, besides the Spanish energetic needs (which causes that this country demands more oil than non-oil products from Mexico), results on the impossibility of a commercial diversification from Mexico to Spain.

En este trabajo se estudian las relaciones comerciales entre México y España y se le da una explicación al fenómeno de la no existencia de diversificación comercial en los productos que México exporta a dicha nación. El trabajo se divide en dos apartados, el primero contiene la respuesta a la formulación de la primera hipótesis de investigación, ésta explica el problema de la diversificación comercial a través de los resultados arrojados por el índice de la Ventaja Comparativa Revelada (VCR), el cual expuso una baja competitividad en los productos mexicanos lo que dificulta la incursión de éstos en el mercado español. El segundo estudio complementa al primero e indica que la necesidad energética española inclina a este país a demandar más de México los productos petroleros que los no petroleros, impidiendo esto que México logre diversificar su exportación a España. Se concluye que la baja competitividad de los productos no petroleros mexicanos más la necesidad energética española que provoca que este país demande más productos petroleros de México que de otra índole, da como resultado la imposibilidad de la diversificación comercial de México hacia España.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2008-0004; España; Comercio; Ventaja comparativa; Demanda; Exportación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/917